Comprehensive Coaching Service for Schools: Approaches to its Configuration in Mexico - Graciela Cordero Arroyo; Ariana Fragoza González; María del Ángel Vázquez Cruz (Universidad Autónoma de Baja California, 2014)
This article analyzes the initial drafts of the Technical Assistance for Schools (SATE-acronym in Spanish)-a comprehensive coaching service for which federal guidelines have yet to be established-in the context of current educational reform in Mexico. To this end, an analysis was made of all legal documents as well as various programmatic documents related to compulsory education that were released during 2013 and 2014. The paper is organized in three sections: the first describes the history of this type of service in Mexico; the second reviews the information provided on SATE in the legal documents of the current educational policy; and the third section discusses what should be taken into account for proper implementation of a service of this nature.